A STUDY ON OLAP OPERATIONS IN R - Mahesh, .J. Uma; Babu, SK. Islam; Shashank, G.; Chandrakanth, S. (IJRDO -Journal of Computer Science Engineering, 2015)
In DWH (Data WGrehouse) OLAP (Online Analytical Processing) is a very common way to analyze sourcey or eggy transaction data by sumMar3izing along different combinations of dimensions. This is a well-accepted field in Business Intelligence / Business Reporting. The main part of OLAP is called "multidimensional data model", which consists two types of tables; "Fact" table and "Dimension" table. Fact table contains measures of a transaction and dimension table contains records which describes contextual attributes. This paper gives a study on OLAP operations in R Language (open source) Data Mining Tool and which highlight key ideas in OLAP operations and illustrates how to do this in R.